Relationship of Factors Causing Perinatal Death in Cianjur Regency - Innama Sakinah (Institute of Computer Science (IOCS), 2022)
he perinatal mortality rate is one of the biggest contributors to the high infant mortality rate. Most of the causes of perinatal mortality 2/3 come from preventable causes, including patient factors, health workers, referrals and health facilities. The purpose of this study was to analyze and explore the factors causing perinatal mortality, barriers to the referral process as well as recording and reporting. The research design used a sequential explanatory design with a combination method approach which was carried out in stages with a quantitative approach in the first stage, namely in the form of data collection from data recapitulation and perinatal verbal autopsy (OVP) as many as 287 perinatal deaths in Cianjur Regency in 2015. The second stage with a qualitative approach through deep interview. The results of this quantitative study showed that most of the perinatal deaths were preventable as many as 245 cases (85.4%) with a period of stillbirth 136 cases (47.4%) and early neonatal 151 cases (52.6%). Factors related to perinatal mortality were found in patient factors, namely basic education 85.4% (p=0.003), history of ANC 4 times 73.9% (p=0.056), and causes of infant mortality, namely stillbirth 47.3% and asphyxia 19.5% (p=0.001). The results of the qualitative study obtained education factors with basic education, history of ANC 4 times, causes of stillbirth and risky asphyxia, geographically in highland areas.